The pathological and outcome characteristics of renal lesions in Crohn’s disease - Zhihui Yang; Xiaochang Xu; Yejing Dong; Yimin Zhang (BMC Nephrology, 2022)
Abstract Background The inflammatory bowel disease, containing Crohn’s disease and ulcerative colitis, was rare in the population, especially in the complication of kidney disease. A few studies had found proteinuria played a potential indicator of inflammatory bowel disease occurrence and activity. This study aimed to better define the histopathologic spectrum and study the outcome of renal disease in Crohn’s disease. Methods A retrospective study of 3557 Crohn's disease from January 1st, 2016 to July 1st, 2021 in the Sixth Affiliated Hospital of Sun Yat-sen University identified 20 (0.56% [20/3557]) patients who underwent kidney biopsy. All biopsy specimens were examined by standard procedures containing light microscopy, immunofluorescence, and electron microscopy. Results Twenty cases were shown in this review study. Subnephrotic proteinuria (30% [6 of 20]), persistent hematuria and proteinuria (25% [5 of 20]), and isolated hematuria with acanthocytes (25% [5 of 20]) were the main indications for kidney biopsy. The most common diagnosis was IgA nephropathy (70% [14/20]), followed by minimal change disease (10% [2/20]), acute interstitial nephritis (5% [1/20]), granulomatous interstitial nephritis (5% [1/20]), non-IgA mesangial proliferative nephritis (5% [1/20]) and thin basement membrane nephropathy (5% [1/20]). The Lee classification of IgA nephropathy was mostly II or III level. Glomerular mesangial hyperplasia was the most common pathologic manifestation according to the MEST-C Sore. After twelve-month treatment, the majority of patients turned to complete remission of renal disease by measuring proteinuria, while 3 patients still stayed in the relapse stage and 6 patients turned to partial remission by measuring hematuria. Conclusions IgA nephropathy is the most common kidney biopsy diagnosis in Crohn's disease. Renal damage in Crohn's disease mainly involves the glomerulus, especially the mesangial matrix. After the treatment, proteinuria might be in remission, but hematuria remains.